Apixaban Dose Selection in Kidney Failure: Reconciling Pharmacokinetics and Clinical Outcomes - Soon H. Yang (Annals of Pharmacotherapy, 2026)
Objective: To compare pharmacokinetic, clinical outcomes, and regulatory evidence for apixaban 5 mg versus 2.5 mg twice daily in kidney failure on hemodialysis with atrial fibrillation (AF), and propose a framework for individualized dose selection. Data Sources: PubMed, EMBASE, and the Cochrane Library were searched from inception through June 2026 using terms including apixaban, kidney failure, hemodialysis, AF, pharmacokinetics (PK), and dosing. Study Selection and Data Extraction: PK studies, observational cohorts, randomized controlled trials (RCTs), network meta-analyses, regulatory documents, and guidelines evaluating apixaban dosing in kidney failure and AF were included. Data Synthesis: Five PK studies (n ≈ 112) showed 2.5 mg twice daily produced steady-state levels comparable to 5 mg in normal renal function, while 5 mg produced approximately 3-fold supratherapeutic exposure. Of the 3 observational studies, 2 linked 5 mg to lower mortality; 1 found 63% higher bleeding with 5 mg and no difference in stroke/systemic embolism (subdistribution hazard ratio (SHR) 1.01; 95% CI, 0.59-1.73) or death (hazard ratio [HR] 1.03; 95% CI, 0.77-1.38). Two RCTs (RENAL-AF and AXADIA-AFNET 8) were terminated early and remain underpowered. Confounding by indication, competing risk of death, and misapplication of dose-reduction criteria likely explain this paradox. Relevance to Patient Care and Clinical Practice: This review provides the first systematic reconciliation of this paradox, identifying confounding by indication, competing risk of death, and structural flaws in the US Food and Drug Administration (FDA) dose-reduction criteria as likely explanations for the discordance. It gives clinical pharmacists a framework for appraising the evidence rather than defaulting to the FDA label or PK data alone, and proposes a decision algorithm for individualized dosing, derived from expert opinion, PK, and observational data and requiring prospective validation. Conclusions: The optimal apixaban dose in kidney failure remains unresolved. Neither dose has been shown to reduce stroke versus no anticoagulation in this population. Dose selection should be individualized to patient-specific factors.